Taxation of platform economies: the new global challenge - Ulas, Gabriela (DIXI, 2020)
Description: The platform economy represents the new challenge of the law of our time, especially at the tax level and in its international aspect. When we talk about platforms, we are not referring to a new concept, but to a new modality of what is called “shared economy”. Thus, in the shared economy we find a long-standing commercial form whose objective is to achieve interaction between consumers or between producers and consumers directly and without resorting to traditional companies or businesses to satisfy their needs. The platform economy has detected this reality and, using new technologies, has adapted it for its promotion through applications on smartphones and other devices so that a certain service reaches more users and as quickly as possible. Findings: At present, approaches are emerging about the employment relationship that originates between those who actually provide the service and the platform company that serves as an intermediary and connects borrowers with consumers. Conclusion: New criteria should be implemented in the interpretation of the concept of “permanent establishment” in order to ensure that platforms are taxed in the States where they effectively provide the intermediation service.